2012
DOI: 10.1186/1476-069x-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits, ambulance calls, and mortality associated with an exceptional heat wave in Sydney, Australia, 2011: a time-series analysis

Abstract: BackgroundFrom January 30-February 6, 2011, New South Wales was affected by an exceptional heat wave, which broke numerous records. Near real-time Emergency Department (ED) and ambulance surveillance allowed rapid detection of an increase in the number of heat-related ED visits and ambulance calls during this period. The purpose of this study was to quantify the excess heat-related and all-cause ED visits and ambulance calls, and excess all-cause mortality, associated with the heat wave.MethodsED and ambulance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
124
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 38 publications
13
124
0
Order By: Relevance
“…Impacts were strongest felt by disadvantaged communities and older people (Loughnan et al 2010;Tong et al 2014). In Sydney in 2011, a severe heatwave resulted in 13% higher rate of mortality, mostly among the elderly (Schaer et al 2012). A more recent multiday heatwave in January 2014 aected state-wide areas of southeast Australia, surpassing the 2009 record, with the average maximum temperature in Victoria exceeding 41°C on four successive days (Australian Government 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Impacts were strongest felt by disadvantaged communities and older people (Loughnan et al 2010;Tong et al 2014). In Sydney in 2011, a severe heatwave resulted in 13% higher rate of mortality, mostly among the elderly (Schaer et al 2012). A more recent multiday heatwave in January 2014 aected state-wide areas of southeast Australia, surpassing the 2009 record, with the average maximum temperature in Victoria exceeding 41°C on four successive days (Australian Government 2014).…”
Section: Introductionmentioning
confidence: 99%
“…15 Many studies focus only on the impact of one severe event and do not establish the impact of the full spectrum of heatwave events, ignoring less intense heat events that are more frequent. 16,17 The full characterisation of this relationship can be used to establish thresholds for heatwave response plans based on the impact on health services, and to establish formulas that demonstrate a dose-response relationship.…”
mentioning
confidence: 99%
“…The impact of extreme weather on the number of ambulance 999 calls has been reported in many studies but is rarely quantified [1][2][3][4][5][6][7][8]. These studies show a significant increase in the number of calls during periods of extreme weather (e.g., heat waves, cold waves).…”
Section: Introductionmentioning
confidence: 81%
“…In further studies, Mahmood et al [3] analyzed the impact of air temperature on London ambulance call-out incidents and response times and Nitschke et al [4] analyzed the impact of two extreme heat episodes on morbidity and mortality in Adelaide, South Australia. Schaffer et al [5] examined emergency department visits, ambulance calls, and mortality associated with the 2011 heat wave in Sydney, Australia. They concluded that the heat wave resulted in an increase in the number of emergency department visits and ambulance calls, particularly in older persons, as well as an increase in all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%